2015
DOI: 10.1186/s13638-015-0293-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-complexity WLMMSE channel estimator for MB-OFDM UWB systems

Abstract: Widely linear (WL) minimum mean square error (MMSE) channel estimation scheme have been proposed for multiband orthogonal frequency division multiplexing ultra-wideband (MB-OFDM UWB) systems dealing with non-circular signals. This WLMMSE channel estimation scheme provides significant performance gain, but it presents a high computational complexity compared with the linear one. In this paper, we derive an adaptive WLMMSE channel estimation scheme that significantly reduces the computational complexity. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Equations (28), (30), (31), and (32) into (26) give the WLMMSE channel estimator in the general case which suppose that the transmitted signals are selected from improper constellation.…”
Section: Wlmmse Channel Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Equations (28), (30), (31), and (32) into (26) give the WLMMSE channel estimator in the general case which suppose that the transmitted signals are selected from improper constellation.…”
Section: Wlmmse Channel Estimationmentioning
confidence: 99%
“…The WL processing has gained a growing interest in the past few years. It has been shown that it provides performance improvement in both cases: when dealing with improper signal constellations and when STBCs are used on the transmitter side . In this paper, we focus on the second case.…”
Section: The Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation